DAMPAK BUDAYA ORGANISASI, DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI PT. BANK MANDIRI (PERSERO), TBK AREA JEMBER - Muhammad Nur Holis; Yunita P. Dewi; Endri Purnomo (Valuasi : Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2022)
The reason for this review is to determine the impact of authoritative culture and responsibility on commitment to implementation in Bank Mandiri Jember Area employees. Researchers used a purposive testing strategy on 35 employees at the Operation & Support Unit of Bank Mandiri Jember Area. This review uses a quantitative review with an explanatory research approach. The strategy used in this study is a quantitative technique with data collection using an overview of opinion polls, documentation studies, and meetings to obtain information needed for 35 independent employees of the operation and support unit. The examination used in this examination uses a linear regression review as well as other examiners. Furthermore, the data that has been obtained from filling out questionnaires, documentation studies, and interviews with respondents were tested using linear regression review. The results show that the authoritative culture directly affects the implementation of Bank Mandiri Jember Area employees. and responsibility for commitments directly affect the implementation of Bank Mandiri Jember Area employees